Toward the formation of a Companion Animal Parasite Council for the Tropics (CAPCT) - Rebecca J. Traub; Peter Irwin; Filipe Dantas-Torres; Gabriela Pérez Tort; Norma Vollmer Labarthe; Tawin Inpankaew; Mukulesh Gatne; Bui Khanh Linh; Volker Schwan; Malaika Watanabe; Susanne Siebert; Norbert Mencke; et al. (Parasites & Vectors, 2015)
Abstract This letter advises the imminent formation of the Companion Animal Parasites Council for the Tropics (CAPCT). The CAPCT consists of region-specific (e.g., Asia-Pacific, Latin America and Caribbean, Africa) experts comprising academics, veterinarians, parasitologists, physicians and allied industry partners that will work together to inform, guide and develop best-practice recommendations for the optimal diagnosis, treatment and control of companion animal parasites in the tropics, with the aim of protecting the health of pets and that of the public.